Dopustnost podaljšanja koncesij - Štemberger Brizani, Katja (Podjetje in delo, 2024)
The article discusses the admissibility of the extension of concessions in Slovenian law considering the constitutional requirements and EU law. The extension of a concession is equated with the procedure of granting a new concession, and therefore in both cases a public tender must normally be held. However, EU law has already established certain exceptions, which should be interpreted restrictively, as the extension of the concession to the existing concessionaire excludes competition and affects the principle of transparency and equal treatment of all potential bidders. This applies both to concessions governed by primary EU law and to concessions subject (only) to the principles of EU law. The authors note that several different forms of concession extension can be found in Slovenian law. However, most of them are constitutionally incompatible or do not comply with the requirements of EU law. The authors therefore conclude that a change towards a more restrictive regulation of this institution is needed, and, in this respect, they make some suggestions for future regulation.
Keywords: call for tenders; CJEU; Directive 2014/23/EU; Direktiva 2014/23/EU; extension of concessions; javni razpis; načelo enakega obravnavanja; podaljšanje koncesij; principle of equal treatment; protection of competition; SEU; transparency of the procedure; transparentnost postopka; varstvo konkurence